Analysis of the Influence of Competence, Workload and Job Stress on the Implementation of Occupational Safety and Health (OSH) among Employees at the Ngadirejo Sugar Factory in Kediri - Kurnianti, Nur Rochmah; Indasah, Indasah; Ambarika, Rahmania (DIKKESH : Jurnal Penelitian Pendidikan dan Kesehatan, 2026)
The successful implementation of an Occupational Safety and Health Management System (OSHMS) in high-risk industries, such as sugar manufacturing, is determined not only by the completeness of formal systems but also by human factors at the operational level. This study aims to analyze the influence of competence, workload, and job stress on the implementation of OSHMS among production employees at the Ngadirejo Sugar Factory in Kediri. A quantitative research design with a cross-sectional approach was employed. A total of 109 employees were selected from a population of 150 using simple random sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results indicate that job stress has a positive and significant effect on OSHMS implementation (β = 0.329; p = 0.004), whereas competence (β = −0.062; p = 0.643) and workload (β = 0.119; p = 0.275) do not show significant effects. Simultaneously, the three variables explain 10.1% of the variance in OSHMS implementation (R² = 0.101), suggesting that other factors outside the model play a more dominant role. The findings suggest that job stress may function as a driver of alertness that enhances compliance with safety procedures in the operational context of Ngadirejo Sugar Factory. Managerial implications emphasize the importance of adaptive stress management, not to eliminate stress entirely, but to maintain it at an optimal level that supports safe work behavior while preventing long-term fatigue and burnout.